The Heat Exchanger Performance of Shell and Multi Tube Helical Coil as a Heater through the Utilization of a Diesel Machine’s Exhaust Gas - . Zainuddin; Jufrizal Nurdin; Eswanto Is (Graduate Program of Syiah Kuala University, 2016)
A review on reutilization of heat waste from a diesel machine is absolutely important. This is because the exhaust gas potential of a Diesel machine keeps increasing and not much has been utilized by the industry. One of the techniques of reutilizing the heat waste in industry is by using a heat exchanger. The technique is also very useful for the environment because it can reduce air pollution caused by the exhaust gas of the diesel machine. The main purpose of the research is to find out the capability of shell and multi-tube helical coil HE as an air heater by utilizing the exhaust gas of the Diesel machine. The heat exchanger of shell and multi-tube helical coil utilizes the exhaust thermal gas of the Diesel machine as the air heater already made. The apparatus has the following dimension: the shell length of 1.05 m, diameter 0.1524 m, tube length of 3.25 m with 20 coils, tube diameter of 0.011 m, coil diameter of 0.0508 m with 4 helical coils. The type of Diesel machine to use in the testing is 4FB1 Isuzu Diesel engine. The machine has the maximum machine power and rotation of 54 kW and 3,600 rpm. The performance testing of heat exchanger has been conducted in some variations of Diesel machine rotations of 1,500 rpm, 1,750 rpm, 2,000 rpm, 2,250 rpm and 2,500 rpm. The testing result shows a maximum effectiveness to happen at the machine rotation of 1,500 rpm. The maximum effectiveness to get is 67.8% and then it goes down drastically in accordance with the increase of air mass flow rate. The hot air temperature created is from 47.1°C to 52.3°C so that it can be used for the purpose of drying up the unhulled rice.